Toward~a differentiated understanding of the effect of Nutri-Score nutrition labeling on healthier food choices - Birgit Gassler; Claudia K. Faesel; Anke Moeser (Agribusiness, 2022)
By 2022, the European Commission seeks to introduce harmonized, mandatory front-of-pack (FOP) nutrition labeling. The color-graded Nutri-Score is at the heart of the European debate. Yet, little is known about how the information provided in back-of-pack (BOP) nutrition tables interacts with evaluative FOP labels, such as Nutri-Score, and if different consumer groups use both information cues differently when making food choices. Our objective is thus to identify segments of nutrition label users and contrast their choice behavior and use of FOP and BOP nutritional information. Therefore, this study builds on an attitude-based segmentation analysis and a survey-based discrete choice experiment among German consumers. We identify five segments of nutritional information users and significant interaction effects between FOP and BOP nutritional cues. Consumers use supplementary nutritional information differently: relying on BOP nutrition facts only (label-resisters) or combining both information cues (majority). For most, Nutri-Score reinforces the positive effect of a healthier nutrient profile on purchase likelihood, while its use stigmatizes products of low nutritional quality. Overall, supplementary Nutri-Score labeling enables better alignment of food choices and health preferences, especially for consumers overwhelmed by technical BOP nutrition tables, and helps differentiate products with relatively unhealthy nutritional profiles. We discuss implications for food policy and business. [EconLit citations: D12, Q13, Q18].
Keywords: 630; back-of-pack nutrition table; choice experiment; consumer behavior; front-of-pack nutrition label; healthy food choice